(untitled) (Revista científica Olimpia, 2020)
In this research we are focus in the preparation of the muscular strength in the Granma´s first category pitchers and in the results obtained after the application of the exercises with medicinal balls to foster the specific strength in the action of throwing. We took into account that the movements in the baseball pitchers are characterized for prevalence in the speed-combined strength. The muscles work during the activity is fundamentally explosive on it is principal phase, however during some moments in the game, the muscles develop statics tensions, but really short ones, the movements potency in the exercise of throwing should be considered determinant in the game, but always with explosive. The Baseball contributes with the development of the capacities, conditionals and coordinating, also it contributes with the raising of specific exigencies in the motor apparatus. The pitchers must guarantee the increasing in the explosive strength of the muscles that take part in the action of throwing, all of this will permit better throwing potency, location in the wished zone, better organization in the movement structure, direction in the throwing, durability in the game, consistency and of course taking advantage over the batters during the game. The main objective of this type of strength is the increasing in the contraction speed of those decisive musculature or conclusive for the competitive performance in the respective sport.